PENGARUH PEMBANGUNAN PELABUHAN TERMINAL INTERNASIONAL KIJING PADA PERUBAHAN KONDISI SOSIAL EKONOMI MASYARAKAT, - Rahmayati, Fitri; Tampubolon, Budiman; Cristanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2023)
This study aims to describe the condition of the construction of the Kijing International Terminal in terms of existing land use and to describe the positive and negative effects of the development of the Kijing International Terminal on the socio-economic community in Sungai Kunyit Village, Sungai Kunyit District, Mempawah Regency. The method used in this research is descriptive quantitative and qualitative. This research was carried out in all areas of the Kijing Terminal development. Data collection methods are observation, interviews, documentation, and accuracy testing. The data analysis technique used is spatial and descriptive analysis. The data sources in this study are Google Earth, Geospatial West Kalimantan, observation, and interviews. The results of this study are descriptions of existing land use conditions using kappa accuracy calculations with a value of 88.87%, this kappa accuracy value is included in the appropriate category. The results of the description of the positive influence of the construction of the Kijing International Terminal on the socio-economic community, namely the many business opportunities to improve the economy of the people in Sungai Kunyit Village, and the description of the negative effects of the construction of the Kijing International Terminal on the socio-economic community in Sungai Kunyit Village, namely the increase in residents from outside the village who live for worked on a terminal construction project in Sungai Kunyit Village, Sungai Kunyit District, Mempawah Regency.